Incidence, Risk Factors and Outcomes of Sepsis in Critically Ill Post-craniotomy Patients: A Single-Center Prospective Cohort Study - Zhou, Jianfang; Luo, Xu-Ying; Chen, Guang-Qiang; Li, Hong-Liang; Xu, Ming; Liu, Shuai; Yang, Yan-Lin; Shi, Guangzhi; Zhou, Jian-Xin; Zhang, Linlin (Frontiers in Public Health, 2022)
Background Data concerning the epidemiology of sepsis in critically ill post-craniotomy patients are scarce. This study aimed to assess the incidence, risk factors, and outcomes of sepsis in this population. Methods This was a single-center prospective cohort study. Post-craniotomy patients admitted to the intensive care unit (ICU) were screened daily for the presence of infection and sepsis. Results Of the 900 included patients, 300 developed sepsis. The cumulative incidence of sepsis was 33.3% [95% confidence interval (CI), 30.2–36.4%]. Advanced age, male, hypertension, trauma, postoperative intracranial complications, and lower Glasgow Coma Scale (GCS) on the first postoperative day were independent risk factors of sepsis. Septic patients had higher hospital mortality (13.7 vs. 8.3%, P = 0.012), longer ICU length of stay (LOS) (14 vs. 4 days, P < 0.001), longer hospital LOS (31 vs. 19 days, P < 0.001), and higher total medical cost (CNY 138,394 vs. 75,918, P < 0.001) than patients without sepsis. Conclusion Sepsis is a frequent complication in critically ill post-craniotomy patients. Advanced age, male, hypertension, trauma, postoperative intracranial complications, and lower GCS on the first postoperative day were independent risk factors of sepsis.